Enzymatic production of ethyl esters from castor oil - Claudia Delgado; Vaselina Pashova (Revista Facultad de Ingeniería Universidad de Antioquia, 2012)
iodiesel synthesis through transesterificación of castor oil with ethanol using n-hexane as a solvent and a lipozyme TL IM commercial lipase as a biocatalyst was studied. The effect of ethanol molar relation to oil (3:1-10:1), temperature of reaction (35-65ºC), initial enzymatic charge (5-20% p/p) and amount of water (0-10% p/p) was investigated. The maximum percentage of bio-diesel (ethyl-esters) was obtained at a temperature of 35ºC, a 5:1 ethanol to oil molar ratio, an initial enzymatic charge of 15 % p/p and an initial water concentration of 2% p/p, both of them based on the castor oil weight. A simplified model was proposed to describe the enzymatic kinetics of castor oil transesterification with ethanol, based on the ping-pong Bi Bi mechanism with competitive inhibition for alcohol. The kinetic parameters of the model were estimated graphically and parametrically; a good approach among the results foreseen by the model and experimental data was found at low ethanol concentration (40-80 mol Kg-1).